The genus Calliphora (Diptera: Calliphoridae) in Argentina, with the first records of C. lopesi Mello 1962 - Olea, María Sofía (2013)
The genus Calliphora Robineau-Desvoidy 1830 is currently represented by only 6 species in the Neotropical Region of which 3 are present in Argentina. In this work, we report for the first time the presence of Calliphora lopesi Mello 1962 in Argentina, and we present an updated distribution of the species of the genus. We provide a key to the identification of the species present in the country.